Gradient Ageing Of Ni-Rich Niti Shape Memory Alloy - Razali, Muhammad Fauzinizam (2013)
To date, the shape memory behaviour are limited only for discrete action application leaving no option for any progressive or intermediate state of control. The creation of gradient plateau is one of the best solutions and it is possible by many ways, and one of it is by microstructure modification via heat treatment that includes annealing and ageing. The purpose of this study is to create a functionally graded NiTi wire with an optimum pseudoelastic behaviour through a gradient ageing treatment. This approach is based on the sensitivity of the alloys’ thermomechanical properties with respect to temperature and duration of ageing treatment. The experimental works are divided into two stages. The first stage involved the study of the effect of temperature and duration of isothermal ageing on thermal and deformation behaviour of NiTi shape memory alloys. Due to the heterogeneous precipitate distribution, prolonged ageing led to the gradient deformation on the isothermal aged specimen with respect to gradual variation of Ni composition within the alloy matrix. The result shows that the stress plateau of the phase transformation exhibits positive stress gradient with a value of 3.4 GPa.